Uncommon bilateral orbital lesion in leukemic patient: is it cutis leukemia, celullitis or both? Poster Presentation - Case Report - Ophthalmologist - ANINDITA WICITRA; Widiarti S. Soemarno; Lady P. Sukmawidowati; Agassi Suseno Sutardjo; Resti Mulya Sari; Primasari Deaningtyas; Grace Shalmont (Majalah Oftalmologi Indonesia, 2023)
Introduction : Acute Myeloblastic Leukemia can infiltrate any parts of the body including the orbit and periocular area. This article was aimed to report uncommon sign of cutis leukemia representing as orbital cellulitis. Case Illustration : Male, 35 yo with chief complained progressive lesion in his bilateral upper and lower eyelid since 4 days before admission. He felt pain and stingy sensation around lesion. There was history of toothache. He was diagnosed with acute myeloblastic leukemia since 2 month before. Ophthalmology examination showed his visual acuity was 6/6 in both eyes with good ocular motility.His bilateral upper and lower eyelid were edematous and spasm with multiple vesicles, papule and pustule. Conjunctival injection was found in both eyes. The reminder of ophthalmology examination was unremarkable. There were other hyperemic nodules in left mandibulae and right mastoid bone. Laboratory examination showed increased leukocyte, procalcitonin and C-Reactive Protein level. Orbital CT scan revealed edema in cutis and subcutis area in both superior and inferior bilateral palpebra. Board spectrum and anaerobe antibiotic along with steroid were administered intravenously. Biopsy was performed. After two weeks medication, lesion around both palpebra was decreased. Unfortunately, because of his poor systemic condition, he was readministered to our hospital and hospitalized in ICU. He was passed away after 8 days of hospitalization. Discussion : Male patient is more likely to develop orbital infiltration of leukemia, and it necessitates significant morbidity and mortality condition. Conclusion : Leukemia with orbital invasion should bring more awareness from both ophthalmologist and hematooncologist as it indicates more mortality and morbidity.